2019
DOI: 10.1186/s41235-019-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting concealed familiarity using eye movements: the role of task demands

Abstract: Background What can theories regarding memory-related gaze preference contribute to the field of deception detection? While abundant research has examined the ability to detect concealed information through physiological responses, only recently has the scientific community started to explore how eye tracking can be utilized for that purpose. However, previous attempts to detect deception through eye movements have led to relatively low detection ability in comparison to physiological measures. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Our findings are consistent with eye movement research underlining the crucial role of cognitive factors such as degree of familiarity, explicit task instructions and stimulus presentation on attention during visual processing tasks (e.g. Loftus & Mackworth, 1978;Nahari, Lancry-Dayan, Ben-Shakhar, & Pertzov, 2019;Yarbus, 1967). Markers of recognition for personally familiar non-face items in Experiment 2 were not as robust as those observed for faces in Experiment 1 (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with eye movement research underlining the crucial role of cognitive factors such as degree of familiarity, explicit task instructions and stimulus presentation on attention during visual processing tasks (e.g. Loftus & Mackworth, 1978;Nahari, Lancry-Dayan, Ben-Shakhar, & Pertzov, 2019;Yarbus, 1967). Markers of recognition for personally familiar non-face items in Experiment 2 were not as robust as those observed for faces in Experiment 1 (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Ben-Shakhar & Elaad, 2003 ; Meijer et al, 2014 ). However, few studies have assessed the robustness of fixation measures during informed countermeasures to conceal recognition (Millen & Hancock, 2019 ; Peth et al, 2016 ; Nahari et al, 2019 , this issue). Whereas Millen & Hancock ( 2019 , this issue) found that fixation durations were largely robust to intentional eye movement strategies to look at every face the same way, Nahari et al ( 2019 ) found that fixation duration as a marker of recognition in simultaneous displays of faces (one familiar face to many unfamiliar faces) vanished when participants were instructed to look at all faces equally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parallel display was divided to two periods of times (1000 ms and 4000 ms) based on our previous studies(Lancry-Dayan et al, 2018;Nahari et al, 2019).1894 LANCRY-DAYAN, NAHARI, BEN-SHAKHAR, AND PERTZOV This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
mentioning
confidence: 99%
“…In addition to orienting, there is evidence of an arousal inhibition effect that is applied by the subjects to conceal their orienting activity, and its measure is used for detecting deception 22 . Typically, CIT measures physiological responses such as heart rate and skin conductance 19 , neural responses, primarily the P300 brain wave 23 , as well as eye movements, eye blinks, and pupil dilation 24 27 . These measures typically require a serial repetitive presentation for averaging; as a result, false positives could occur due to an arbitrary orienting and to the observer’s fatigue as well as biological noise, affecting the signal-to-noise ratio (SNR) as in the P300 BCI methods 28 .…”
Section: Introductionmentioning
confidence: 99%